Allocation of Financial Resources from EARDF in the Context of Typology of Slovak Regions - BACULÁKOVÁ, Kristína; HARAKAĽOVÁ, Ľubica (Journal of Environmental Management and Tourism, 2018)
The Common Agricultural Policy of the European Union (CAP EU) is one of the common EU policies that support vulnerable and disadvantaged EU regions. The allocation of EU structural funds is for a long time considered unequal and unjust. Especially money from European agricultural fund is not distributed directly to farmers. In the paper, we use cluster analysis to define the distribution of funds from the EAFRD (European Agriculture Fund for Rural Development) to individual regions of the Slovak Republic at NUTS 3 level in the previous programming period 2007 – 2013. The main objective of the paper is to identify the regions where most of the money form EARDF was allocated during this period. The results of the cluster analysis are clear - funds were not concentrated only in regions that are classified as predominantly rural (according the OECD methodology) but also in regions that were classified as intermediate or even predominantly urban.